Challenges and Innovative Strategies in 3D Printing of Natural Biomolecular Hydrogels - Jiaqi Qiu; Shuo Ma; Xue Qu (Nano Select)
ABSTRACT Natural biomolecules with excellent biocompatibility, degradability, and the ability to guide effective tissue regeneration are considered ideal materials for constructing tissue engineering hydrogel scaffolds. The employing of 3D printing technology facilitates the preparation of natural biomolecular‐based scaffold for specific morphological requirements for tissue engineering. However, there are significant limitations in the precise manufacturing of such scaffolds using extrusion‐based 3D printing technology. In this review, we put forward the challenges encountered in the 3D printing process using natural biomolecular inks. Building upon this, we summarize and discuss strategies commonly employed to enhance the printing performance of natural biomolecular inks, including inducing rapid ink cross‐linking, improving ink rheological properties, incorporating auxiliary inks for shaping, flexibly controlling ink extrusion, and optimizing printing equipment. Furthermore, this review offers a perspective on the future design and development of printing technologies based on natural biomolecular inks.